Analysis of the Influence of Meta AI Usage on the Learning Interests of Informatics Education Students - Mone, Surya Saputra; sogen, Maria Magdalena Beatrice; Wagur, Vidiyanto; Paju, Benediktus Kurniawan (JUPE : Jurnal Pendidikan Mandala, 2025)
This study analyzes the influence of Meta AI usage on the learning interest of Informatics Education students in the digital era. The main issues addressed are the suboptimal integration of Meta AI in learning processes and students’ readiness to adapt to new technologies. Using a mixed-method approach, data were collected through questionnaires and  with second and fourth-semester students. The results indicate that Meta AI significantly enhances learning interest, facilitates information access, and boosts students’ motivation and curiosity. However, challenges regarding technology dependence and privacy issues remain. This research provides recommendations for developing adaptive and effective Meta AI-based learning strategies in higher education.